Performance of Kampong Chicken Fed Rations With Suplementing Dry Carboxylate Salt Mixture (DCM) or Coconut Oil Hydrolisate (COH) - Tasse, Andi Murlina; Aka, Rahim; Malesi, La; Auza, Fuji Astuty; Achmad, Diska Bintayani; Sambolinggi, Salomina (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
The experiment aimed to know effect of supplementing dry carboxylate salt mixture (DCM)or coconut oil hydrolisate (COH) on kampong chicken performance. The experiment used DOC whichis divided to is 75 units henhouse with 3 treatments and 5 replications. Each unit consist of 5 DOCand fed treatments during 8 weeks. The treatments were T1 (commercial ration = BP-1), T + 3%DCM), and T3 (T + 3% COH). The variables were daily feed intake, weekly gain, feed conversion,carcass weight, gizzard weight, liver weight, and heart weight. The data analysis used ANOVA andorthogonal contrast test. The results showed that daily feed intake (g/d), T112 = 53.52 ± 3.00 =38.86 ± 5.12± 1.22, T3b, T3 = 50.72 ± 6.41a, weekly gain (g/week) T = 10.72 ± 6.41, feed conversion T11 = 17.41 ± 4.80, T = 6.11 ± 1.24, T22 = 3.92 ± 1.06, T = 18.89 ± 2.77, T = 5.71 ± 1.09, carcassweight (kg) T1 = 75 ± 19.33c, T2 = 345.50 ± 19.33b, T3 = 377.0 ± 10.55a3, gizzard weight (g) T = 10.75 ±0.5, T2 = 12.13 ± 0.25, T3 = 13.13 ± 0.25, liver weight T1 = 10.6 ± 0.81, T2 = 13.1 ± 0.05, T = 16.63 ±0.48, heart weight T1 = 2.4 ± 0.25, T2 = 3.3 ± 0.29, T = 4.0 ± 0.41. It can be concluded that (1) supplementing 3% dry carboxylate salt mixture (DCM in the ration improve weekly gain and feedconversion ; (2) supplementing 3% coconut oil hydrolisate (COH) in the ration improve carcassweight, gizzard weight, liver weight, and heart weight.Key Words: Dry Carboxylate Salt Mixture (DCM), Coconut Oil Hydrolisate (COH), Kampoeng Chicken, Performance 313 (T31a, T2 = 16.22